Analysis of concentration and sedimentation of suspended load in the reservoirs - Dolinar, Bojana (Acta geotechnica Slovenica, 2008)
This paper deals with the sedimentation of suspended load in the reservoirs. As an example the reservoir of the hydroelectric power plant Boštanj on the Sava River is shown. The objective of the described studies was to determine the quantity and type of deposited material in the reservoir during the selected time period. For this purpose, the mineral and chemical composition, and the concentration and the particle size of the suspended load at the intake of the water into the reservoir and at its outflow were examined. In order to determine the concentration of the suspended load, 24 water samples from the area of the intake and outflow from the reservoir were taken. At the same time the discharge of the Sava River was measured. Solid particles were removed from the water with the help of sedimentation and in the final stage of water evaporation. The results of the studies showed that the concentration of the suspended material was changing in relation to the location and the flow rate of the water. This ratio can be described with an exponential function. In suspended load composition carbonates, muscovite/illite and quartz dominate; however, chlorite was also found, as well as small quantities of plagioclase and organic detritus. With regard to the size of the particles the examined samples are classified as silt. It was determined that the concentration of the suspended load, at the same flow rate of water, at the intake into the reservoir is larger than at the outflow. The difference is represented by the material that was sedimented in the reservoir due to the decreased speed of the water as a result of the river's impoundment. A comparison of the composition of the samples from both collection sites showed that at the outflow site of the water from the reservoir there is a somewhat smaller share of carbonate grains and heavy minerals than at the intake site, and a higher content of organic detritus and clay particles can also be observed. Considering the actual discharge of water in the period between July 2006 and July 2007 and the examined ratio between the flow rate of the water and the quantity of suspended and deposited material, the total quantity of sedimented material in this period was estimated.
Keywords: Boštanj; jezera; rečne naplavine; sedimentacija